PENGEMBANGAN MODEL AUTHENTIC ASSESSMENT DALAM PERKULIAHAN METODE PENELITIAN PENDIDIKAN - suciati rahayu widyastuti (Procediamath, 2018)
THE DEVELOPMENT OF AUTHENTIC ASSESSMENT MODELS IN CLASS OF EDUCATION RESEARCH METHOD. Abstract Educational research methodology is designed so that students can understand educational research methods, review educational journals, make research instruments, compile research proposals, sample drawings, and analyze data processing research. The standard of achievement is based on the competence of SN-DIKTI graduates which includes attitudes, knowledge and skills. So that the development of an appropriate type of assessment is an authentic assessment model. The purpose of this study in the subject of educational methodology is (1) to develop an authentic assessment model; (2) analyzing the validity of authentic assessment models; (3) analyzing student responses to authentic assessment models; (4) analyzing the differences of student learning outcomes that use the results of the development of an authentic assessment model with students who do not use the results of the development of an authentic assessment model. This research is a type of Research &Development (R & D).The population of this study were FKIP students in Cirebon, UNU Cirebon. Sampling of cluster random sampling. Data collection methods that will be carried out are interviews, documentation, observation, tests, and questionnaires. The instrument of collection data in the form of device validation sheets, interviews, student response questionnaires, observation, and tests. Abstrak. Metodologi penelitian pendidikan dirancang agar mahasiswa dapat memahami metode penelitian pendidikan, mereview jurnal pendidikan, membuat instrumen penelitian, menyusun proposal penelitian, penarikan sampel, dan analisis pengolahan data penelitian. Standar pencapaiannya berdasarkan kompetensi lulusan SN-DIKTI yang mencakup sikap, pengetahuan, dan keterampilan. Sehingga pengembangan jenis penilaian yang sesuai yaitu model authentic assessment. Tujuan penelitian ini pada mata kuliah metodologi pendidikan adalah (1) mengembangkan model authentic assessment; (2) menganalisis kevalidan model authentic assessment; (3) mengalisis respon mahasiswa terhadap model authentic assessment; (4) menganalisis perbedaan hasil belajar mahasiswa yang menggunakan hasil pengembangan model authentic assessment dengan mahasiswa yang tidak menggunakan hasil pengembangan model authentic assessment. Penelitian ini merupakan jenis Research & Development (R&D). Populasi penelitian ini adalah mahasiswa FKIP di Cirebon UNU Cirebon. Pengambilan sampel cluster random sampling. Metode pengumpulan data yang akan dilakukan adalah wawancara, dokumentasi, observasi, tes, dan kuesioner. Instrumen pengumpulan data berupa lembar validasi perangkat, wawancara, angket respon mahasiswa, observasi, dan tes.Kata kunci : Pengembangan, Model Authentic Assessment, Metode Penelitian Pendidikan